Complete plastome sequence of Piper laetispicum (Piperaceae): An endemic plant species in South China - Ming-Tao Wang; Jian-Hua Wang; Kun-Kun Zhao; Zhi-Xin Zhu; Hua-Feng Wang (Mitochondrial DNA. Part B. Resources, 2018)
Piper laetispicum is dioecious climbers woody with 10 m tall, which is an endemic species in China. It grows on trees or rocks in forests (100–600 m) in Guangdong and Hainan Province of China. Here, we report and characterize the complete plastid genome sequence of P. laetispicum in an effort to provide genomic resources useful for promoting its conservation. The complete plastome is 161,721 bp in length and contains the typical structure and gene content of angiosperm plastome, including two inverted repeat (IR) regions of 27,125 bp, a large single copy (LSC) region of 89,224 bp and a small single copy (SSC) region of 18,247 bp. The plastome contains 114 genes, consisting of 80 unique protein-coding genes, 30 unique tRNA gene, and four unique rRNA genes. The overall A/T content in the plastome of P. laetispicum is 61.70%. The complete plastome sequence of P. laetispicum will provide a useful resource for the conservation genetics of this species as well as for the phylogenetic studies for Piper.